Peritumoral SPARC expression and patient outcome with resectable intrahepatic cholangiocarcinoma - Yeh, Chun-Nan; Cheng, Chi-Tung; Huang, Shih-Chiang; Chen, Ming Huang; Tsai, Chun-Yi; Chen, Yen-Yang; Ma, Ming-Chun; Liu, Chien-Ting; Chen, Tsung-Wen; Yeh, Ta-Sen; Chu, Yin-Yin; Chiang, Kun-Chun; et al. (OncoTargets and therapy, 2015)
Cholangiocarcinoma (CCA) affects thousands worldwide with increasing incidence. SPARC (secreted protein acidic and rich in cysteine) plays an important role in cellular matrix interactions, wound repair, and cellular migration, and has been reported to prevent malignancy from growth. SPARC undergoes epigenetic silencing in pancreatic malignancy, but is frequently expressed by stromal fibroblasts adjacent to infiltrating pancreatic adenocarcinomas. CCA is also a desmoplastic tumor, similar to pancreatic adenocarcinoma. SPARC's clinical influence on clinicopathological characteristics of mass-forming (MF)-CCA still remains unclear. In this study, we evaluate the expression of SPARC in tumor and stromal tissue to clarity its relation with prognosis. Seventy-eight MF-CCA patients who underwent hepatectomy with curative intent were enrolled for an immunohistochemical study of SPARC. The expression of immunostaining of SPARC was characterized for both tumor and stromal tissues. We conducted survival analysis with 16 clinicopathological variables. The overall survival (OS) was analyzed by Kaplan-Meier analysis and Cox proportional hazards regression modeling. Thirty-three men and 45 women with MF-CCA were studied. Within total 78 subjects, 12 (15.4%) were classified as tumor negative/stroma negative, 37 (47.4%) as tumor positive/stroma negative, four (5.1%) as tumor negative/stroma positive, and 25 (32.1%) as tumor positive/stroma positive. With a median follow-up of 13.6 months, the 5-year OS was 14.9%. Cox proportional hazard analysis revealed that SPARC tumor positive and stromal negative immunostaining and curative hepatectomy predicted favorable OS in patients with MF-CCA after hepatectomy. MF-CCA patients with SPARC tumor positive and stromal negative expression may have favorable OS rates after curative hepatectomy.